Pengaruh Functional Value, Emotional Value & Social Value Promosi Media Sosial Terhadap Keputusan Pembelian Tamu di Grand Rocky Hotel Bukittinggi - Gyvel Melvani Putri; Youmil Abrian; Witra Neldi (Departemen Pariwisata Universitas Negeri Padang, 2026)
The use of social media as a promotional tool in the hospitality industry is expected to create functional value, emotional value, and social value that influence guests’ purchasing decisions. Fluctuations in occupancy rates and cancellations at the Grand Rocky Hotel Bukittinggi indicate that guests’ purchasing decisions are not yet stable. This study aims to analyze the influence of functional value, emotional value, and social value on guests’ purchasing decisions at the Grand Rocky Hotel Bukittinggi. This study employs a quantitative approach with a causal-associative research design. The research sample consisted of 180 respondents selected using the [specify sampling technique] method. Data were collected through the distribution of questionnaires. Descriptive analysis was used to describe the levels of functional value, emotional value, social value, and purchasing decisions, while multiple linear regression analysis was used to test the influence of the three independent variables on purchasing decisions. The results show that Functional Value (X1) achieved a TCR value of 81.4% in the “good” category, Emotional Value (X2) achieved 82.5% in the “good” category, Social Value (X3) achieved 81.2% in the “good” category, and Purchase Decision (Y) achieved 84.7% in the “very good” category. Partially, functional value has a positive and significant effect on purchase decision (β = 0.344; p = 0.003), emotional value has a positive and significant effect (β = 0.302; p = 0.004), and social value has a positive and significant effect (β = 0.449; p < 0.001). Simultaneously, all three variables had a significant effect on purchasing decisions (p < 0.001). The adjusted R-squared value of 0.683 indicates that functional value, emotional value, and social value account for 68.3% of the variation in purchasing decisions, while the remainder is influenced by other variables outside the research model. The results of this study are expected to serve as a basis for the management of the Grand Rocky Hotel Bukittinggi in developing more effective digital promotion strategies to increase guests’ purchasing decisions.